Infant feeding among HIV-positive mothers and the general population mothers: comparison of two cross-sectional surveys in Eastern Uganda - Tylleskär Thorkild; Semiyaga Nulu B; Wamani Henry; Engebretsen Ingunn MS; Fadnes Lars T; Tumwine James K (BMC, 2009)
Abstract Background Infant feeding recommendations for HIV-positive mothers differ from recommendations to mothers of unknown HIV-status. The aim of this study was to compare feeding practices, including breastfeeding, between infants and young children of HIV-positive mothers and infants of mothers in the general population of Uganda. Methods This study compares two cross-sectional surveys conducted in the end of 2003 and the beginning of 2005 in Eastern Uganda using analogous questionnaires. The first survey consisted of 727 randomly selected general-population mother-infant pairs with unknown HIV status. The second included 235 HIV-positive mothers affiliated to The Aids Support Organisation, TASO. In this article we compare early feeding practices, breastfeeding duration, feeding patterns with dietary information and socio-economic differences in the two groups of mothers. Results Pre-lacteal feeding was given to 150 (64%) infants of the HIV-positive mothers and 414 (57%) infants of general-population mothers. Exclusive breastfeeding of infants under the age of 6 months was more common in the general population than among the HIV-positive mothers (186 [45%] vs. 9 [24%] respectively according to 24-hour recall). Mixed feeding was the most common practice in both groups of mothers. Solid foods were introduced to more than half of the infants under 6 months old among the HIV-positive mothers and a quarter of the infants in the general population. Among the HIV-positive mothers with infants below 12 months of age, 24 of 90 (27%) had stopped breastfeeding, in contrast to 9 of 727 (1%) in the general population. The HIV-positive mothers were poorer and had less education than the general-population mothers. Conclusion In many respects, HIV-positive mothers fed their infants less favourably than mothers in the general population, with potentially detrimental effects on both the child's nutrition and the risk of HIV transmission. Mixed feeding and pre-lacteal feeding were widespread. Breastfeeding duration was shorter among HIV-positive mothers. Higher educational level and being socio-economically better off were associated with more beneficial infant feeding practices.